Instrumental delivery and ultrasound : a multicentre randomised controlled trial of ultrasound assessment of the fetal head position versus standard care as an approach to prevent morbidity at instrumental delivery. - MURPHY, DEIRDRE (My University, 2014)
OBJECTIVE: To determine whether the use of ultrasound can reduce the incidence of incorrect diagnosis of the fetal head position at instrumental delivery and subsequent morbidity. DESIGN: Two-arm, parallel, randomised trial, conducted from June 2011 to December 2012. SETTING: Two maternity hospitals in the Republic of Ireland. SAMPLE: A cohort of 514 nulliparous women at term (≥37 weeks of gestation) with singleton cephalic pregnancies, aiming to deliver vaginally, were recruited prior to an induction of labour or in early labour. METHODS: If instrumental delivery was required, women who had provided written consent were randomised to receive clinical assessment (standard care) or ultrasound scan and clinical assessment (ultrasound). [Correction added on 17 April 2014, after first online publication: Sentence was amended.] MAIN OUTCOME MEASURE: Incorrect diagnosis of the fetal head position. RESULTS: The incidence of incorrect diagnosis was significantly lower in the ultrasound group than the standard care group (4/257, 1.6%, versus 52/257, 20.2%; odds ratio 0.06; 95% confidence interval 0.02-0.19; P < 0.001). The decision to delivery interval was similar in both groups (ultrasound mean 13.8 minutes, SD 8.7 minutes, versus standard care mean 14.6 minutes, SD 10.1 minutes, P = 0.35). The incidence of maternal and neonatal complications, failed instrumental delivery, and caesarean section was not significantly different between the two groups. CONCLUSIONS: An ultrasound assessment prior to instrumental delivery reduced the incidence of incorrect diagnosis of the fetal head position without delaying delivery, but did not prevent morbidity. A more integrated clinical skills-based approach is likely to be required to prevent adverse outcomes at instrumental delivery.
PUBLISHED
Keywords: Obstetrics